STUDENTS’ PERFORMANCE, SATISFACTION, ACCEPTANCE AND USE OF TECHNOLOGY, AND BEHAVIORAL INTENTION DURING THEIR BLENDED LEARNING EXPERIENCE: A CASE IN A STATE UNIVERSITY IN CAGAYAN VALLEY, PHILIPPINES - MARIA CECILIA G. UY, DME , ROWENA R. STO. TOMAS, PHD (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Blended Learning (BL) is characterized with onsite and online modes of instruction employing benefits from both modalities widely used during the COVID-19 Pandemic. The researchers looked into how the students’ performance during their BL is affected by their level of satisfaction and their perceived acceptance and use of technology in their BL during the pandemic employing a descriptive correlational approach and using a questionnaire to collect data from a sample of 320 students from all the four colleges. Data were analyzed using Pearson-r, t-test, and ANOVA and multiple linear regression to identify predictors of students' BL performance. Results showed that students' overall Satisfaction with their BL is high with high levels of Satisfaction with their teachers, technology, course management, and engagement in BL, and moderate satisfaction with instruction; that all seven constructs of Unified Theory of Acceptance and Use of Technology (UTAT2) are correlated positively significant with students’ Behavioral Intention (BI) to use BL; that the students' Academic Performance and their BI to use technology as well as their Satisfaction with BL have significant positive relationships and that both BI and Satisfaction with BL contribute to significant improvements to students’ Academic Performance. Therefore, the combination of BI and Satisfaction with BL are valuable factors in understanding and in influencing students' Academic Performance in BL classrooms implying that there are learners who may perform better or worse in a BL setting due to their BI and levels of Satisfaction thus recognizing and addressing these factors can have a significant effect on educational outcomes.